2017
DOI: 10.11648/j.ijae.20170202.11
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Factors as Determinants of Farm Management Skills Among Broiler Poultry Producers in Botswana

Abstract: Abstract:When considering the importance of farm management, poor growth and challenges in poultry production, it is important to analyze and understand the current level of the managerial skills and the factors influencing these skills. This descriptive and co-relational study analyzed socio-economic factors influencing farm management skills among broiler poultry producers in Botswana. A valid and reliable questionnaire was used for data collection through a survey of 60 randomly sampled broiler poultry farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
1
4
0
3
Order By: Relevance
“…In addition to being a learning medium, organizations are a medium for farmers to have access to and develop the market. This is in line with the governments' policy in improving farmer abilities through the strengthening of farmer institutions (Baliyan and Marumo, 2016).…”
Section: Factors That Influenced the Broiler Farmers' Business Capacitysupporting
confidence: 76%
See 1 more Smart Citation
“…In addition to being a learning medium, organizations are a medium for farmers to have access to and develop the market. This is in line with the governments' policy in improving farmer abilities through the strengthening of farmer institutions (Baliyan and Marumo, 2016).…”
Section: Factors That Influenced the Broiler Farmers' Business Capacitysupporting
confidence: 76%
“…In the broiler housing aspect, for instance, the farmers mostly used broiler houses raised on stilts, not on the ground, even though the most recent recommended technology was the closed house system. A similar assessment was given by the Extension Agent Coordinator of the Bogor Regency Animal Husbandry Agency (Baliyan and Marumo, 2016).…”
Section: Farmers' Capacity Levelmentioning
confidence: 97%
“…Todsadee et al (2012) stated that increasing broiler production in Chiang Mai Province could be obtained by adopting good management practices. Baliyan & Masuku (2017) found that to increase the efficiency and productivity of broiler farming, small-scale broiler breeders must be adequately trained in management skills.…”
Section: Production Of Broilermentioning
confidence: 99%
“…According to Baliyan and Masuku (2017), the criteria for livestock size in this study were divided into three levels, namely low (0 -5,000 head), medium (5,001-10,000 head) and high (> 10,000 head). The complete data regarding total livestock size are presented in Table 8.…”
Section: Livestock Sizementioning
confidence: 99%